The Bessel wavelet transform of distributions in D′L2-type space - Amit; Maurya J.S.; Upadhyay S.K. (My University, 2025)
In this paper, the inversion formula and the continuity of the continuous Bessel wavelet transform of distributions in DL2′- type space are investigated. For the uniqueness of the inversion formula, the Bessel wavelet kernel of nonvanishing moments is considered. © 2023 World Scientific Publishing Company.